The Reality of Buffalo Breeding in Basra Governorate - Tabeekh, Mudhar A.S. Abu; Abdul Mohsen, Hamed Abdul Majid Abdul; Jaberi, Amal A. Al (Journal of Buffalo Science, 2017)
Buffaloes in Iraq represent the most productive animal since its domestication in Mesopotamia about pre-historic era. Domestic water buffalo (Babalus Babalis) are common in the marshes of southern Iraq. On Sunday the UN cultural agency, UNESCO, added the marshlands and the ancient Sumerian cities that once flourished among them to its list of sites. The marshes today remain one of the poorest areas. Residents living on tiny floating islands fish, tend water buffalo and gather reeds. Little published research could be found into the numbers or environmental impacts of water buffalo in Basra governorate. One of the research objectives was to survey the water buffalo in this region including Al Dear, Al Hartha, Abu Alkhasib, Shat Alarab, Al Qurna, Al Mdainah, Imam Sadiq, Imam Qaim, Al Faw, Al Nshwa, Al Zubair and in Basra center. This study was conducted to evaluate all aspects of the river buffalo for the period from 2012-2016. Comprehensive knowledge of the breed characteristics, its population size and structure, taxonomy, geographical distribution and most important diseases is required to have effective management. As the marsh Arabs or Ma’adan complain of problems with some common buffalo diseases, such as those infecting the hoofs and the tongue, providing of veterinary services would be of critical value for buffalo breeding from an economical prospective.